Fostering Smart People In Jakarta Smart City: Embracing The Betawi Worldview - Fathy, Rusydan; Pramadi, Yoka; Ramadhan, Indra Surya (Universitas Negeri Semarang, 2023)
Smart city, both in terms of academic concepts and practical implementation, is a strategic discourse because it involves various disciplines. In this discourse, the relationship between technological infrastructure and human resources is increasingly dynamic and finds many variations at the local and national levels. This article examines the relevance of cultural elements within the Jakarta Smart City program. Specifically, it aims to explore the process of fostering smart people who align with the Betawi people's outlook on life, which can be or has been affirmed in Jakarta Smart City. The concept of smart people is widely discussed in conceptual debates and smart city practices. To conduct this study, a qualitative approach was employed, utilizing data collection methods such as interviews and focus group discussions. The findings of this research reveal that certain stigmas or stereotypes towards the Betawi people contradict their actual perspectives on life. However, these perspectives can potentially contribute to the formulation and implementation of smart community programs within the context of Jakarta Smart City. Common threads between the two include tolerance, religiosity, and education. Based on these findings, it is suggested that smart city policies need to be formulated in a more contextual and relevant manner to address the daily practices and needs of the community. In other words, smart city policies should be developed through a bottom-up approach, allowing for targeted implementation of community issues.